When reality backfires: Product evaluation context and the effectiveness of augmented reality in e-commerce - Alexander Pfaff; Martin Spann (Psychology & Marketing, 2023)
Augmented reality (AR) enables consumers to project product holograms into their surrounding real-world context in real time using their mobile devices. Although AR may improve online consumers' product evaluation, AR-deploying retailers give up control over the context in which their products are evaluated. As a result, AR retailers' products might end up being evaluated in unfavorable contexts, such as disorganized rooms. Negative spillover effects from such unfavorable AR contexts onto the perceptions of evaluated products may lead consumers to refrain from purchasing the products. In two online experiments and a controlled field study with a total of 1000 participants, we find that unfavorable AR contexts negatively affect consumers' product-related purchase intention. This relationship is serially mediated by processing disfluency and deteriorating product quality perceptions of consumers. The negative contextual effects are mitigated if the product under evaluation is of unique design and thus more conceptually fluent or if the AR context becomes less perceptually salient and thus the product more perceptually fluent. We discuss diminished reality and facilitated product comparisons via AR as potential countermeasures for AR retailers and provide suggestions for future research.
Keywords: 650; augmented reality; field study; perceptual salience; processing fluency; product design uniqueness; product evaluation context; product quality